2020
DOI: 10.1039/d0ra04736h
|View full text |Cite
|
Sign up to set email alerts
|

Cerium oxide nanoparticles: properties, biosynthesis and biomedical application

Abstract: Cerium oxide nanoparticles have revolutionized the biomedical field and is still in very fast pace of development. Hence, this work elaborates the physicochemical properties, biosynthesis, and biomedical applications of cerium oxide nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
115
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(119 citation statements)
references
References 201 publications
(230 reference statements)
1
115
0
3
Order By: Relevance
“…NMs can act as bioreceptors as well as transducers. For example, cerium oxide-based NMs exhibit biomimetic catalytic activity favorable for bioreceptors [ 69 ]. Due to their effective transduction capabilities, different inorganic materials, such as graphene and CNTs-based NMs, noble metal NPs, and QDs, have successfully been used as transducers.…”
Section: Biosensormentioning
confidence: 99%
“…NMs can act as bioreceptors as well as transducers. For example, cerium oxide-based NMs exhibit biomimetic catalytic activity favorable for bioreceptors [ 69 ]. Due to their effective transduction capabilities, different inorganic materials, such as graphene and CNTs-based NMs, noble metal NPs, and QDs, have successfully been used as transducers.…”
Section: Biosensormentioning
confidence: 99%
“…It is a convenient material for treating ROS mediated disorders such as neurogenerative disorder, retinal disorder, cancer, and inflammation, and others [ 39 , 40 ]. It is observed that CeO 2 acts as a catalyst that mimics the features of antioxidant enzymes such as superoxide dismutase (SOD), catalase, and oxidase, in terms of scavenging ROS and free radicals [ 31 , 41 , 42 ]. Nanoceria has been reported to cause selective toxicity towards human lung cancer cells and prostate cancer cells but has shown no toxicity to normal cells (L929).…”
Section: Features Of Metal Oxides Related To Biomedical Applicatiomentioning
confidence: 99%
“…The biological synthesis of CeO2-NP was performed according to the common methods reported in the literature [6][7][8] yet with some modifications and optimization in the synthesis effectiveness variable, including the cerium salt concentration, extract volume, temperature, and time. Optimizations in the process of synthesizing CeO2-NP was based on achieving the highest absorption spectra intensity within 300-330 nm (due to charge transfer from O2P to Ce4f orbitals) [31], which was measured and recorded by a UV-Vis spectrophotometer.…”
Section: Biosynthesis Of Ceo2-npmentioning
confidence: 99%
“…In addition, the CeO2 prepared with these methods is toxic and unstable, reducing its efficiency [4,5]. Accordingly, in recent decades, a safe, non-toxic, eco-friendly, and low cost approach, known as biological (green) synthesis, is used by researchers for production of metal oxide nanoparticales, including CeO2 [6][7][8]. This approach employs various biological resources such as plants, microbes, or any other biological derivative (primary and secondary metabolites) believed to lead to reduction and stabilization.…”
Section: Introductionmentioning
confidence: 99%